Vitamin D, Falls and Balance Capacity Impacts in Older Adults: Update - Ray, Marks (Journal of Aging Research And Healthcare, 2021)
Background Falls injuries continue to contribute to numerous premature deaths as well as high disability levels, and excess morbidity rates among older adults, worldwide. But can vitamin D account for excess falls injuries among older adults? This review specifically focuses on what is known about vitamin D in the context of postural stability or balance control, both fairly consistent independent predictors of falls among older adults. Methods and Procedures Drawn largely from a review of current relevant English language peer reviewed research publications published over the last 10 years detailing the relationship between vitamin D levels and balance control among the elderly, as this relates to falls injuries, evidence for any emerging consensus on this controversial topic was sought. Used to conduct the search were various key word combinations including: falls injuries and older adults, vitamin D or vitamin D deficiency and balance or postural control. The database used predominantly to provide input into this largely descriptive assessment and narrative overview was PUBMED. Results The prevailing data show falls injuries currently constitute a widespread costly major impediment to successful aging and longevity for many older adults, despite numerous efforts to prevent this disabling set of events over the past two to three decades. However, no consistent association appears to exist between the variables of vitamin D, falls, and balance attributes in the older population-despite years of research, regardless of study approach, and a strong rationale for hypothesizing a clinically meaningful relationahip. Conclusion It is not possible to arrive at any universal recommendation concerning the value of vitamin D supplementation as regards its possible influence on balance capacity among older adults in the realm of falls prevention efforts, as has been frequently proposed. However, until more definitive research is conducted, there still appears sufficient justification for considering the screening of vulnerable aging adults for serum vitamin D levels, along with balance impairments, and intervening as required in the case of deficits in either or both of these possible falls determinants.
Keywords: Balance control; falls; falls injuries; older adults; postural stability; prevention; risk factors; screening; therapeutic use of vitamin D; vitamin D deficiency